The Impact of Electronic Word of Mouth towards Customers Repurchase Intention with e-Trust and E-Loyalty as the Mediator in Indonesian Ride Hailing Industry: A Case of Go-jek - Kevin Darmasaputra (iBuss Management, 2021)
Electronic Word of mouth (eWOM) has changed the fundamental ofmarketing, especially the e-commerce industry. Go-jek (written as Gojek) is a multiservice and digital payment platform founded by Nadiem Makarim, an Indonesian citizen who studies at Harvard University and co-founded by Michaelangelo Moran in 2010. Go-jek is the first ‘Decacorn’ company in Indonesia. Researchers are focusing on the use of Eletronic Word of Mouth that Go-jek has used. In this research, the researcher wants to examine whether quality,quantity, content, intensity can influence repurchase intention of Go-jek. Moreover, this research also examines whether e-trust and e-loyalty act as a mediation between those variables towards online repurchase intention. The researcher has collected 80 valid research data obtained from the questionnaires distributed on Google form.The data are then analyzed with Partial Least Square Structural Equation Modeling (PLS-SEM). The result of the data analysis concluded that eWOM quantity, quality, e-trust, and e-loyalty can affect online repurchase intention. In addition the resultalso found that eWOM content and intensity does not significantly affect online repurchase intention (ORPI). Keywords: Electronic Word of Mouth, Quality, Quantity, Content, Intensity, e-Trust, e-Loyalty, Online Repurchase Intention